Perancangan Sistem Kontrol Tekanan Pada Reaktor Biogas Berbasis PID Controller dengan Ziegler-Nichols dan Auto Tuning PSO - Abdurrakhman, Arief; Sutiarso, Lilik; Ainuri, Makhmudun; Ushada, Mirwan; Islam, Md Parvez (Jurnal Otomasi Kontrol dan Instrumentasi, 2024)
Biogas, an eco-friendly energy source, significantly reduces greenhouse gas emissions by converting organic waste or biomass into methane. However, the quality of biogas, primarily determined by methane content and pressure variables, directly impacts its efficiency and safety. This study, which aims to design a pressure control system and monitor methane gas levels in a biogas reactor using a PID Controller with Particle Swarm Optimization (PSO), provides crucial insights into improving biogas production efficiency and safety. Tests were conducted on a fixed dome-type biogas reactor in the East Java region, Indonesia. The PSO-based PID tuning was compared with two other PID tuning methods: Trial-error and Ziegler-Nichols (ZN). Data on pressure values and biogas flow rates from the biogas reactor were collected, and system modeling was carried out to produce a system transfer function. The PSO algorithm was developed to optimize PID control parameters. The results of this research demonstrate that the PID tuning method using PSO produces a stable state error value of 1.40%, rise time of 0.09 s, settling time of 2.1 s, maximum overshoot of 0.986404, and ITAE of 0.0010801. The implementation of PID-PSO can significantly enhance PID control performance in rise time, settling time, maximum overshoot, and ITAE compared to Trial-Error and ZN, while the stable state error value in PID-PSO tuning is higher than tuning using Trial-Error and ZN.